Title Relationships and Text Cohesion... in the “Water Hymns” Short Story Collection - Nabaa Hasan Ali Aljumaili; Muhammad Shirin Chenar (Zanco Journal of Human Sciences, 2025)
The study titled "The Relationship Between the Title and Text Cohesion in the Short Story Collection 'Water Chants'" seeks to explore the connection between the title and the structure of the text in the collection by the author Sanaa Shalan. The study is based on three research axes: In the first axis, the researcher discusses critical studies that address the title and its impact on the aesthetics of the text. The second axis focuses on the superficial structure of the text, which has been influenced by the author's accumulated culture. The third axis examines the structural composition of the text and how this aligns the main title with the sub-titles and accompanying texts. The researcher utilized a variety of mechanisms, relying on the verbal level and its structures, in addition to the figurative and semantic levels. Special attention was given to the symbolic dimension and non-linguistic signs, analyzing their impact on the cohesion of the text's structure with the title. All of this aims to guide the reader in exploring new semantic dimensions of the text.